2019
DOI: 10.1002/asjc.2233
|View full text |Cite
|
Sign up to set email alerts
|

Decompositions of finite games: From weighted inner product to standard inner product

Abstract: To investigate the topological structure of finite games, various decomposions of finite games have been proposed. The inner product of vectors plays a key role in the decomposition of finite games. This paper considers the effect of different inner products on the orthogonal decomposition of finite games. We found that only when the compatible condition is satisfied, a common decomposition can be induced by the standard inner product and the weighted inner product simultaneously. To explain the result, we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Han et al [16] investigated the current state estimation problem in partially observed DESs and presented some new criteria for the detectability of DESs via Boolean semi-tensor product (BSTP), which is a generalization of STP in the Boolean domain. In addition, the STP approach has also been applied to other kinds of finite-value systems such as Boolean networks [24][25][26][27][28][29], game theory [30][31][32][33][34], nonlinear feedback shift register [35], and so on [36][37][38]. Please refer to previous works [39][40][41][42][43] for some comprehensive surveys of STP.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [16] investigated the current state estimation problem in partially observed DESs and presented some new criteria for the detectability of DESs via Boolean semi-tensor product (BSTP), which is a generalization of STP in the Boolean domain. In addition, the STP approach has also been applied to other kinds of finite-value systems such as Boolean networks [24][25][26][27][28][29], game theory [30][31][32][33][34], nonlinear feedback shift register [35], and so on [36][37][38]. Please refer to previous works [39][40][41][42][43] for some comprehensive surveys of STP.…”
Section: Introductionmentioning
confidence: 99%